After Coal: Meanings of the Durham Miners' Gala - Tomaney, John (Frontiers in Sociology, 2020)
The annual Durham Miners’ Gala (or ‘Big Meeting’), first held in 1871, was a distinctive feature of the coalfield throughout its productive life. It became an important date in the calendar of national labour movement. But it was also a festival of music and banners. The Durham Miners’ Association represented a crucial component of the British working class and a cornerstone of Labourism. But its distinctive class practices also marked out a region (see Cooke, 1985) with particular political traditions. The last mine closed in 1994. Yet the Gala has survived the demise of industry and the conflicts and struggles which it produced. In July 2019, the 135th Gala attracted tens of thousands of people. This paper reviews the existing academic literature on the Gala and draws on a range of sources (including memoirs, novels, paintings, films, biographies, interviews) to chart the shifting cultural history of the Gala. I show that the form and content of the Gala has changed throughout its history and has been freighted with a range of meanings.. The Gala can be seen as an example of “intangible cultural heritage” in which knowledge of the past aspects of working class and communal life are reproduced and reimagined even when the material basis for them has apparently disappeared.